2020
DOI: 10.1097/j.pain.0000000000001912
|View full text |Cite
|
Sign up to set email alerts
|

Slow depolarizing stimuli differentially activate mechanosensitive and silent C nociceptors in human and pig skin

Abstract: High-threshold mechanosensitive and mechanoinsensitive (“silent”) nociceptors have similar electrical thresholds for transcutaneous sine wave stimulation at 4 Hz that selectively activates cutaneous C nociceptors in human skin. Their fundamentally different functions particularly in chronic pain warrant differential stimulation protocols. We used transcutaneously delivered slow depolarizing stimuli (half-sine, 500 ms duration, 0.01-1 mA) in humans to assess intensity–response relations for the induction of pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…In addition to traditional threshold measures, assessment of C‐nociceptor electrical excitability may broaden the characterization of hypersensitivity in chronic pain patients. Here, we investigated sensitization of C‐nociceptor sub‐classes to NGF using electrical sinusoidal stimulation paradigms (Jonas et al., 2018; Rukwied et al., 2020). We found enhanced axonal excitability of mechano‐sensitive C‐nociceptors to 1 Hz (500 ms half sine) stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to traditional threshold measures, assessment of C‐nociceptor electrical excitability may broaden the characterization of hypersensitivity in chronic pain patients. Here, we investigated sensitization of C‐nociceptor sub‐classes to NGF using electrical sinusoidal stimulation paradigms (Jonas et al., 2018; Rukwied et al., 2020). We found enhanced axonal excitability of mechano‐sensitive C‐nociceptors to 1 Hz (500 ms half sine) stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Intradermal injection of NGF is known to facilitate action potential generation and conduction (Obreja, et al., 2011; Obreja et al., 2018; Rukwied et al., 2014). In order to induce action potential discharge preferentially in nociceptors we designed an electrode (Landmann et al., 2016) and a stimulus profile (Rukwied et al., 2020) to specifically depolarize mechano‐sensitive C‐nociceptors. A half sine wave constant current stimulus provokes a burst of action potentials (Rukwied et al., 2020) and we found that NGF increased the pain ratings to the most intense amplitude of half sine wave stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations